Responsibility of commitment making officials in government procurement of goods/services - J. Bambang Pudjiono,; Slamet Suhartono,; Endang Prasetyawati,; Yovita Arie Mangesti, (Technium Social Sciences Journal, 2024)
The implementation of good governance is the main prerequisite for carrying out state goals, especially in providing public welfare. In line with the large demands of society for the implementation of good governance, the government must provide quality public services. In this regard, development planning is needed that is systematic, directed, comprehensive, and responsive to the dynamics of community needs. In the government's efforts to provide public services, it is necessary to develop and implement a real legal accountability system for the implementation public services, so that the implementation of government and development can take place in an efficient, clean and accountable manner. The responsibility of Commitment Making Officials in the procurement of government goods/services consists of administrative responsibility and criminal responsibility. Administrative responsibility occurs if an administrative violation occurs, and will be subject to administrative sanctions. Meanwhile, criminal liability means the possibility that a criminal act has occurred and can be subject to criminal sanctions. However, this responsibility can also be imposed on other officials involved in the procurement of goods/services, such as Budget Users, Budget User Proxies, Procurement Officials/Election Working Group, as long as their involvement in the criminal act can be proven.